Evaluation of Salivary Interleukin 2 (IL-2) and Interleukin 12(IL-12) in Recurrent Aphthous Stomatitis - Saeed, Sura Farhan; Aldhaher, Zainab Abduljabar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Recurrent aphthous stomatitis (RAS) is a common kind of excruciating mouth mucosal disease. Despite their high prevalence, etiopathogenesis remains unclear. This study was to investigate the concentration of Interleukin 2 (IL-2) and Interleukin 12 (IL-12) in the saliva of RAS. Eighty people were involved In this study (forty RAS patients and forty healthy controls), their ages ranged (from 16 - 60) years. The sandwich enzyme-linked immune-sorbent assay was used to assess Interleukin 2 (IL-2) and Interleukin 12 (IL-12) concentrations in saliva in each group. The salivary concentrations of Interleukin 2 (IL-2) and Interleukin 12 (IL-12) was significantly higher in the patient group (159.06 ± 20.37), (331.32 ± 94.42) respectively in comparison to the control group at (p<0.05). These results indicate that saliva provides the perfect medium for the detection of pro-inflammatory markers of the oral cavity, Additionally, salivary Interleukin 2 (IL-2) and Interleukin 12 (IL-12) may play a significant role in the pathophysiology of this illness.